Cumplimiento de la normatividad vigente de productos farmacéuticos refrigerados en la Distribuidora farmacéutica La Libertad, enero – diciembre 2015 - Alonzo Aguirre, Diana Nataly (2018)
This report was made with the objective of determining compliance with the current regulations of the Law on Pharmaceutical Products, Medical Devices and Health Products No. 29459 and its regulation D.S. No. 016-2011-SA; subject to registration, control and sanitary surveillance of refrigerated pharmaceutical products in a pharmaceutical distributor of La Libertad. The cold chain for refrigerated pharmaceutical products is of vital importance in the conservation and maintenance of its quality, being the storage stage the longest, and where the cold or refrigerated chamber acquires greater importance. These cold chambers correspond to large refrigeration equipment, intended for the storage of pharmaceutical products in a temperature range of 2 to 8 ° C, which is constantly monitored by the use of different devices. During this work the qualification of an adequate storage was made, through the three stages of registration, during which the temperatures were verified in 3 different hours with the manual thermometer, which establishes maximum and minimum temperatures of the Cold Room. In this stage the good performance of the temperature sensor (° C) was demonstrated, which establishes an approximate range to the manual thermometer. And above all, it is linked to the range of 2 to 8 ° C, which indicates adequate storage and a controlled temperature, ensuring that these refrigerated products retain their properties to the end user